Analisis Struktur Modal, Kinerja Manajemen Terhadap Nilai Perusahaan Dengan Manajemen Laba, Kinerja Keuangan Opini Audit Sebagai Variabel Pada Perusahaan - fatwa, muhammad nabil; hwihanus (Publikasi Inspirasi Indonesia, 2024)
Capital Structure Analysis, Management Performance on Company Value with Profit Management, Financial Performance Audit Opinion as a Variable in the Company. This research aims to analyze the influence of capital structure, management performance, earnings management, financial performance and audit opinion on company value. The independent variables used in this research include capital structure as measured by the debt to equity ratio (DER), management performance as measured by return on assets (ROA), earnings management as measured by profitability, financial performance as measured by return on equity (ROE). ), and audit opinion as measured by audit quality. The dependent variable used is company value as measured by price to book value (PBV). The analytical method used is descriptive statistics and multiple linear regression analysis. The research results show that capital structure has a positive and significant effect on company value, management performance has a positive and significant effect on company value, earnings management has a positive and significant effect on company value, financial performance has a positive and significant effect on company value, and audit opinion has a positive and significant effect. significant to company value. Based on the research results, it can be concluded that capital structure, management performance, earnings management, financial performance and audit opinion simultaneously have a significant effect on company value.